Cloning and Molecular Characterization of Plasmid-Encoded Antigens of Borrelia burgdorferi - Skare, Jonathan T. (American Society for Microbiology, 1999)
Thirteen independent clones that encode Borrelia burgdorferi antigens utilizing antiserum from infection-immune rabbits were identified. The serum was adsorbed against noninfectious B. burgdorferi B31 to enrich for antibodies directed against either infection-associated antigens of B. burgdorferi B31 or proteins preferentially expressed during mammalian infection. The adsorption efficiency of the immune rabbit serum (IRS) was assessed by Western immunoblot analysis with protein lysates derived from infectious and noninfectious B. burgdorferi B31. The adsorbed IRS was used to screen a B. burgdorferi expression library to identify immunoreactive phage clones. Clones were then expressed in Escherichia coli and subsequently analyzed by Western blotting to determine the molecular mass of the recombinant B. burgdorferi antigens. Southern blot analysis of the 13 clones indicated that 10 contained sequences unique to infectious B. burgdorferi. Nucleotide sequence analysis indicated that the 13 clones were composed of 9 distinct genetic loci and that all of the genes identified were plasmid encoded. Five of the clones carried B. burgdorferi genes previously identified, including those encoding decorin binding proteins A and B (dbpAB), a rev homologue present on the 9-kb circular plasmid (cp9), a rev homologue from the 32-kb circular plasmid (cp32-6), erpM, and erpX. Additionally, four previously uncharacterized loci with no known homologues were identified. One of these unique clones encoded a 451-amino-acid lipoprotein with 21 consecutive, invariant 9-amino-acid repeats near the amino terminus that we have designated VraA (for “virulent strain-associated repetitive antigen A”). Since all the antigens identified are recognized by serum from infection immune rabbits, these antigens represent potential vaccine candidates and, based on the identification of dbpAB in this screen, may also be involved in pathogenic processes operative in Lyme borreliosis.